Peningkatan Prestasi Membaca Permulaan Melalui Media Gambar dan Sway pada Siswa Sekolah Dasar - Sri Amalia; Nur Afit Azizah B; Silpa Septi Aura B; Ulfayani Hakim (Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to enhance early reading achievement in Grade I students at UPTD SDN 19 Barru through the use of image media and Sway. The research employs Classroom Action Research (CAR) methodology, conducted in two cycles involving 28 students. Data collection techniques include observation, interviews, and documentation, analyzed qualitatively. The findings indicate a significant improvement in students' early reading skills, with the average score rising from 61 in the pre-cycle to 68 in Cycle I and 84 in Cycle II. The integration of image media and Sway effectively increased student engagement and motivation, ultimately leading to better reading outcomes. This research highlights the importance of innovative teaching media in fostering foundational literacy skills.